Упростите выражение 6 + 1 x a(квадрат)+6a+9 ( ------------- -------------------- )...

0 голосов
42 просмотров

Упростите выражение 6 + 1 x a(квадрат)+6a+9
( ------------- -------------------- ) ------------------------------
a(квадрат) - 9 3-a 5


Алгебра (18 баллов) | 42 просмотров
Дан 1 ответ
0 голосов

1)6\а2-9 + (1\3-а)=6\(а-3)*(а+3) -1\а-3 = 6-(а+3) \(а-3)*(а+3)=6-а-3\(а-3)*(а+3)=3-а\(а-3)*(а+3) \-(а-3)\(а+3)*(а-3)=-1\а+3
2)-1\а+3 *(а2+6а+9\5) =-1\а+3*((а+3) в кв \5) = -(а+3)\5=-а-3\5

(22.8k баллов)
0

ой ещё забыл и найти его значение при a=-4

0

при а=-4 ,тогда -(-4)-3\5=4-3\5=1\5=0,2